Late Onset Remnant Gastric Cancer with Afferent Loop Syndrome 47 Years after Billroth II Surgery - Memduh şahin; Bahattin Ozlu; Kivilcim Eren Erdogan; Tahsin Colak (Case Reports in Surgery)
Remnant gastric cancer is a rare clinical entity. Herein we describe a patient with remnant gastric cancer that presented with afferent loop syndrome 47 years after Billroth II surgery. Symptoms of serious bilious vomiting were an indication to perform early endoscopic diagnosis, followed by complete gastric resection. In particular, patients that have undergone surgery due to benign indications should be examined endoscopically, even a long time after initial surgery.